2008
DOI: 10.1029/2007gl032884
|View full text |Cite
|
Sign up to set email alerts
|

Solar forcing and planetary ion escape from Mars

Abstract: [1] The variability of planetary ion escape from Mars is studied using data from the Ion Mass Analyzer, IMA, on Mars Express (MEX). 42 orbits were selected during 17 months for different solar wind conditions, focusing on the low energy (%30 -800 eV) heavy ion (e.g. O + , O 2 + and CO 2 + ) outflow. A strong correlation is found between solar wind forcing of the obstacle, the cross-sectional area enclosing the ion outflow from Mars and the total heavy ion escape flux. The at least one order of magnitude change… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
105
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 88 publications
(118 citation statements)
references
References 20 publications
(23 reference statements)
11
105
1
Order By: Relevance
“…We compare the obtained solar wind dependence of ion escape fluxes with observations. Lundin et al (2008) suggested that there is a strong correlation between the solar wind dynamic pressure and the planetary ion loss rate. They focused on the heavy ions in the energy range of 30-800 eV, and reported that the total escape flux increases from 6.0 × 10 23 to 6.0 × 10 24 s −1 as the solar wind pressure increases from 0.1 to 10 times the nominal value.…”
Section: Discussion and Summarymentioning
confidence: 99%
“…We compare the obtained solar wind dependence of ion escape fluxes with observations. Lundin et al (2008) suggested that there is a strong correlation between the solar wind dynamic pressure and the planetary ion loss rate. They focused on the heavy ions in the energy range of 30-800 eV, and reported that the total escape flux increases from 6.0 × 10 23 to 6.0 × 10 24 s −1 as the solar wind pressure increases from 0.1 to 10 times the nominal value.…”
Section: Discussion and Summarymentioning
confidence: 99%
“…The main mechanisms at work are (Chassefiere & Leblanc 2004;Lundin et al 2007;Lilensten et al 2013): (a) photochemical escape, or dissociative recombination in which the ions produced by UV photoionization, electron impact and charge exchange with the solar wind protons, recombine generating escaping energetic neutrals; (b) pickup ion escape where the ions produced by photoionization are picked up by the solar wind; (c) atmospheric sputtering leading to exospheric neutrals undergoing collisions with energetic ions (mainly O + , initially formed from exospheric photoionization, being picked up and swept away by the solar wind magnetic lines, and finally re-impacting the exobase, provoking secondary escape); (d) hydrodynamic escape (escaping light neutrals transferring momentum to heavier species), particularly during the Early Noachian era (Chassefiere & Leblanc 2004). Therefore, the atmospheric escape at Mars has a strong connection to the solar activity (Luhmann et al 1987;Lundin et al 2008), since the solar EUV flux creates ions that can diffuse through the atmosphere and be picked up by the solar wind. In particular, the EUV solar flux has a strong influence on the atmospheric escape through two main mechanisms: (a) it ionizes and dissociates CO 2 to form CO 2 + , CO + , O + and some minor species such as CO ++ and C + ; these daughter-ions are lighter than the neutral CO 2 and diffuse upward, where a part of them gets picked up by the solar wind; (b) being unstable and highly energetic (i.e.…”
Section: Space Weather At Mars and Venusmentioning
confidence: 99%
“…ASPERA on-board the ESA Mars Express probe (e.g. Lundin et al 1990) showed that Mars is still experiencing atmospheric escape (Dubinin et al 2008), with an escape flux ranging between 2 · 10 24 ions per sec and 3 · 10 25 ions per sec (Lundin et al 1990;Lundin et al 2008;Nilsson et al 2011).…”
Section: Space Weather At Mars and Venusmentioning
confidence: 99%
“…Ion sputtering: exospheric neutrals undergo collisions with energetic ions, picked up and swept away by solar wind magnetic lines, and finally re-impacting the high atmosphere. Mars' atmospheric escape has a strong connection to solar activity (Luhmann et al 1987;Lundin et al 2008): the solar EUV flux creates ions that can diffuse through the atmosphere and are taken away in the solar wind. An additional phenomenon may increase escape: the ions are sensitive to the interplanetary magnetic field and will spiral about the magnetic field lines.…”
Section: A Mixed Particle/radiation Effect: Atmospheric Escape-the Camentioning
confidence: 99%